SILAR Controlled CdS Nanoparticles Sensitized CdO Diode Based Photodetectors - Gozeh, Bestoon Anwer; Karabulut, Abdulkerim; Yildiz, Abdulkadir; Dere, A.; Arif, Bilal; Yakuphanoğlu, Fahrettin (Springer, 2020)
In this research, we have produced Al/CdS nanoparticles-CdO/p-si/Al photodetetor and investigated its optical and electrical characteristics for various optoelectronic applications. The CdO thin film was covered by using sol-gel spin coating method onto the silicon, followed by CdS nanoparticles constitution by the help of SILAR technique. In order to examine the morphological and optical characteristics of fabricated photodetector, the field emission scanning electron microscopy and UV-Vis spectroscopy were utilized, and the band gap of the prepared film was determined as 2,17 eV with the help of these analyzes. The current behavior against the varying voltage values were investigated for the different intensities of solar light conditions and the significant diode parameters were computed by the use of this measurements. As a result of this computation, the barrier height value was found to be 0.49 eV while the ideality factor value was 3.2, and the photoresponse of the photodetector was measured as approximatelly 2.65 x 10(3). Besides, the transient photocurrent and photocapacitance charactersitics were examined for distinct light conditions. Finally, the interface states were calculated from the capacitance/conductance-voltage (C/G-V) measurements.
Keywords: Optical characteristics; CdS nanoparticles; CdO thin film; Electrical characteristics; Sol-gel method; SILAR method